RASIO TULANGAN OPTIMUM PADA BAJA TULANGAN BJTP DAN BJTD BALOK EMPAT PERSEGI PANJANG TULANGAN TUNGGAL - Eri Setia Romadhon (FTSP Universitas Jayabaya, 2022)
What is the optimum reinforcement ratio that can be achieved for plain reinforcing steel (BJTP) and deformed reinforcing steel (BJTD) to obtain the maximum moment of resistance in a single reinforced rectangular beam? The optimum reinforcement ratio is achieved when the moment of resistance reaches the maximum value for a certain optimum reinforcement ratio value. By knowing the optimum reinforcement ratio, it will be very easy to make the most efficient increase in beam strength. This study uses a case study of rectangular beams with various dimensions which are often used in high-rise building projects. At the moment of maximum resistance for single-reinforced rectangular beams, the optimum reinforcement ratio for BJTP steel is 0.0885 and BJTDreinforcing steel is 0.0531.